2016
DOI: 10.1155/2016/7830785
|View full text |Cite
|
Sign up to set email alerts
|

The Brief Symptom Inventory and the Outcome Questionnaire-45 in the Assessment of the Outcome Quality of Mental Health Interventions

Abstract: Self-report questionnaires are economical instruments for routine outcome assessment. In this study, the performance of the German version of the Outcome Questionnaire-45 (OQ-45) and the Brief Symptom Inventory (BSI) was evaluated when applied in analysis of the outcome quality of psychiatric and psychotherapeutic interventions. Pre-post data from two inpatient samples (N = 5711) and one outpatient sample (N = 239) were analyzed. Critical differences (reliable change index) and cut-off points between functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The BSI-53 has been previously used in a community sample (depression: M = 0.42, SD = 0.65, anxiety: M = 0.45, SD = 0.60, hostility: M = 0.44, SD = 0.60) and outpatient sample (depression: M = 1.99, SD = 1.10, anxiety: M = 1.87, SD = 1.03, hostility: M = 1.39, SD = 1.02; Ryan, 2007 ). Previous research has also shown that the BSI-53 is sensitive to intervention-related change (Crameri et al, 2016 ), and the depression, anxiety, and hostility subscales to have acceptable internal consistency and test re-test reliability (Derogatis & Melisaratos, 1983 ). In the current study the measure showed good internal consistency at baseline and follow-up (depression: BL α = .87, FU α = .89; anxiety: BL α = .87, α = .89; hostility: BL α = .81, FU α = .82).…”
Section: Methodsmentioning
confidence: 99%
“…The BSI-53 has been previously used in a community sample (depression: M = 0.42, SD = 0.65, anxiety: M = 0.45, SD = 0.60, hostility: M = 0.44, SD = 0.60) and outpatient sample (depression: M = 1.99, SD = 1.10, anxiety: M = 1.87, SD = 1.03, hostility: M = 1.39, SD = 1.02; Ryan, 2007 ). Previous research has also shown that the BSI-53 is sensitive to intervention-related change (Crameri et al, 2016 ), and the depression, anxiety, and hostility subscales to have acceptable internal consistency and test re-test reliability (Derogatis & Melisaratos, 1983 ). In the current study the measure showed good internal consistency at baseline and follow-up (depression: BL α = .87, FU α = .89; anxiety: BL α = .87, α = .89; hostility: BL α = .81, FU α = .82).…”
Section: Methodsmentioning
confidence: 99%
“…Quality of life and areas of life functioning (symptoms, interpersonal problems, social role functioning) using the Outcome Questionnaire (OQ-45.2) scales in German, applying a cut-off score of >63 for clinically significant compromise [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is a validated self-report questionnaire, which includes a spectrum of psychiatric symptoms. A weighted sum score above 0.75 means that clinically relevant psychopathology symptoms were present [ 33 , 34 ]. In addition, we considered the use of selective serotonin reuptake inhibitors (SSRIs) during pregnancy (the most frequently used antidepressant in our study), which was obtained from pharmacy records and self-reported information [ 35 ].…”
Section: Methodsmentioning
confidence: 99%